Synet på natur og historie hos Grundtvig og Løgstrup - Henningsen, Hans (Grundtvig-studier, 1994)
The View of Nature and History in Grundtvig and Løgstrup By Hans Henningsen Grundtvig’s and K.E. Løgstrup’s thoughts move in two different dimensions, but with the same intention of demonstrating that it was not the capacity of man to create culture that first gave significance to the world. But where Grundtvig speaks about history, Løgstrup speaks about »phenomena«, »nature«, and »universe«.While Grundtvig was largely unaffected by Kant, the latter - with his concepts of the selfexistent subject and the idea of the faculty of cognition as productive - became a challenge to Løgstrup. Kant heralds an era whose relationship with the universe is characterized as a »marginal existence«. Our culture became an emancipatory culture which was all to the good, but the era lost its sense of the .pre-cultural. structures in which life is »encased«.The era has also emancipated itself from Grundtvig’s historical view. But a history on the premisses of relativism is no history. Or, in Løgstrup’s words, there is no other history than the history of what is essential in life. Therefore, in reality, Løgstrup’s phenomenological and philosophical endeavours become a defence of history. Grundtvig’s view of nature was determined by his radical prioritization of history. He prefers to view nature as part of the historical life of man, which again determines his use of nature images. In Grundtvig there is no religious interpretation of any experience or perception of nature in spite of the fact that everything in the Creation is to be understood as images of the eternal.In Løgstrup there is no such cautions attitude towards nature. Here nature and sense perception are liberating, but as is the case with Grundtvig, nature is seen as the foundation of man’s life, as immediate experience.Grundtvig’s radical prioritization of history colours his view of art. The Creation itself is the greatest work of art; part of it is the upbringing through which all history must be the object of the individual’s own experience. Among the art forms, poetry ranks highest, with the song above all other forms, while Grundtvig only uses disparaging words about painting and sculpture because these art forms are wordless and preclude changes. Løgstrup, however, attaches much greater importance to sense perception and self-recognition through art.These contrasts may be regarded as what Løgstrup calls uniting opposites; it must be remembered, however, that such disparities cannot be harmonized so as to disappear, but are uniting precisely by virtue of the tension that exists between them. The actual existence of the contrasts does not preclude the possibility that in a wider sense the two views may be contained within the same framework and express a common intention.